Methodological aspects of modernization of professional training of future music teachers - KOZYR, A.; LABUNETS, V.; PANKIV, L.; LIMING, W.; GEYANG, ZH. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The paper reports the experience of implementing an innovative methodological model of professional training of future music teachers. The basic methods and forms of pedagogical experimental works in Kamianets-Podilsky Ivan Ohienko National University are presented. The reliability of the data was confirmed by the results of final processing according to the diagnostic methods of the confirmatory experiment. 67 students with bachelor and specialist degrees specializing in music were prepared according to the 4-stage methodological model of innovative instrumental-performing training. The results can serve as a model for preparing future music teachers for innovative instrumental-performing activity.